Interventions and support strategies psychosocial for orphans of PLHIV admitted to care structures in the Katoka Health Zone by caregivers and counselors for social and educational inclusion. (REVUE DES SCIENCES DE LA SANTE, 2026)
This study examined the support provided to orphans of people living with HIV in the Katoka Health Zone. Findings indicate that while some emotional and educational needs are addressed, support delivery lacks consistency. The absence of targeted training among staff members negatively impacts the effectiveness of care. Statistical analysis highlights staff training as a significant factor influencing the continuity of support. Beneficiaries expressed mixed opinions, revealing a need to strengthen interpersonal interactions and communication. Finally, systemic barriers such as limited staff and financial constraints continue to undermine the success of current support strategies. These outcomes align with the study’s initial assumptions.
Keywords: Support strategies; interventions; orphans of PLHIV; care institutions; caregivers; counselors; social and educational inclusion